2021
DOI: 10.7759/cureus.15211
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Results of the Triathlon Knee Replacement: A Cohort Study

Abstract: IntroductionStudies evaluating the outcomes of different brands of knee prostheses are important to monitor patient outcomes and generate evidence to aid decisions around the choice of implant. The Triathlon® prosthesis (Stryker, Limerick, Ireland), one of the most commonly used total condylar knee prosthesis, is designed to provide greater knee motion and the potential for longer implant survivorship. The aim of this cohort study was to evaluate outcomes and survivorship of the Triathlon total knee replacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…Our study shows significantly lower rates of revision-free implant survival at 5 years in patients less than age 40 years (77.2%), 40 to 49 years (88.9%), and 50 to 59 years (91.7%) when compared with population aged 60 to 79 years (>95%). These implant-survival rates are markedly lower in the less than 40 years and 40 to 49 years groups compared to the general TKA population in the literature, which show 5-year implant survival greater than 96.5% [13,22,27,29,30]. Five-year implant-survival rates in patients above 60 years of age in our study are consistent with those previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…Our study shows significantly lower rates of revision-free implant survival at 5 years in patients less than age 40 years (77.2%), 40 to 49 years (88.9%), and 50 to 59 years (91.7%) when compared with population aged 60 to 79 years (>95%). These implant-survival rates are markedly lower in the less than 40 years and 40 to 49 years groups compared to the general TKA population in the literature, which show 5-year implant survival greater than 96.5% [13,22,27,29,30]. Five-year implant-survival rates in patients above 60 years of age in our study are consistent with those previously reported.…”
Section: Discussionsupporting
confidence: 91%
“…However, in most TKA cases, implant survival beyond 5 years seems to decrease and since the follow-up of these patients in ongoing, it would be interesting to observe the overall survivorship and rate of revision TKA in these cohorts. 21,22 In a retrospective analysis of patients grouped age-wise reported higher rates of revision and 23% revision rates at 5 years, significant higher readmission rates (within 90 days) in younger cohort (younger than 40, 40-49, 50-59). 19 However, in our prospective study, none of the patients younger than 55 or 55 to 65 were readmitted to hospital for post-TKA related issues.…”
Section: Discussionmentioning
confidence: 99%
“…A minimum of 6 months postoperative follow-up was chosen for surgical studies to assess chronic pain, as earlier research has reported the largest pain improvement 3 to 6 months after, eg, total knee arthroplasty surgery. 61 Pharmacological and exercise-based studies were included if they investigated long-term effects of therapy (weeks/months), whereas studies focused on the acute effects of pharmacological or exercise-based therapies were excluded. In addition, the exclusion criteria consisted of languages other than English, conference abstracts, and animal studies.…”
Section: Methodsmentioning
confidence: 99%